Potential of symbiotic and non-symbiotic legume endophytes as plant growth promoting bacteria (PGPB). - Mohd Saud, Halimi; M. K., Nur Hasnidar
Legumes play an important role in providing nitrogen in ecological system. Numerous symbiotic and non-symbiotic endophytic bacteria have been isolated from root nodules of many types of legume plants (Zakhia et al. 2006: Kan et al. 2007: Palaniappan et al. 2010). Rhizobia-legume is an example of symbiotic endophylcs which are able to supply ammonia to the legume plants by fixing nitrogen in the atmosphere.